Mild encephalopathy with reversible lesions in the splenium of corpus callosum and bilateral cerebral deep white matter in identical twins - Junko Tahara; Jun Shinozuka; Hitoshi Awaguni; Shin-ichiro Tanaka; Shigeru Makino; Rikken Maruyama; Shinsaku Imashuku (MDPI AG, 2016)
Identical twin brothers developed mild encephalopathy at the age of 7.0 and 9.7 years (Patient 1) and 10.7 years (Patient 2). Patient 1 had influenza A at the time of his second episode, but triggering agents were not evident at the first episode. The triggering agents in Patient 2 were unclear. The neurological features of both patients included transient facial numbness, left arm paresis, dysarthria, and gait disturbance. Diffusion-weighted images from magnetic resonance imaging showed high signal levels at the splenium of corpus callosum and in the bilateral cerebral deep white matter. These results are characteristic of mild encephalitis/encephalopathy with a reversible isolated splenium of corpus callosum lesion. All three episodes were treated with a methylprednisolone pulse. Acyclovir was also administered to Patient 2 and to Patient 1 during his first episode. Patient 1 received an anti-influenza agent and intravenous immunoglobulin during his second episode. Both patients recovered completely without sequelae. Genetic factors, which may predispose identical twins to develop encephalopathy, are discussed.